Developing the Talents and Creativity of Students - Veleriy Thilavongsa; Peter Phoumai; Souvandee Souvandee (Newinera Publisher, 2020)
This paper aims to discuss the relationship between talent, creativity and achievement. Talent can affect a person's achievement so that he is able to make achievements, in addition to realizing talent, it is necessary to have extensive knowledge, experience and motivation that support that talent. A person with supportive talent and creativity is able to score good achievements because someone with talent and creativity that is developed from an early age will be realized in the form of superior achievements. They are able to develop their talents through their unlimited creativity so that they can make superior achievements.